2017
DOI: 10.1091/mbc.e17-05-0326
|View full text |Cite
|
Sign up to set email alerts
|

Manganese-induced trafficking and turnover of GPP130 is mediated by sortilin

Abstract: By binding and directing the cycling Golgi protein GPP130 to lysosomes, the sorting receptor sortilin mediates the manganese-induced GPP130 down-regulation that protects against Shiga toxicosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…This hypothesis is supported by the presence of sortilin in SPG15 pulldowns and its reduction in vesicle-enriched preparations from AP-5 knockout cells. In addition, while this manuscript was in preparation, Vencat and Linstedt reported that the Mn 2+ -induced exit of GOLIM4 from the Golgi is dependent on sortilin, and they suggested that the lumenal domains of the 2 proteins interact with each other [ 38 ]. However, the additive effects of sortilin knockdown and AP-5 knockout indicate that AP-5 can also act in a sortilin-independent manner.…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis is supported by the presence of sortilin in SPG15 pulldowns and its reduction in vesicle-enriched preparations from AP-5 knockout cells. In addition, while this manuscript was in preparation, Vencat and Linstedt reported that the Mn 2+ -induced exit of GOLIM4 from the Golgi is dependent on sortilin, and they suggested that the lumenal domains of the 2 proteins interact with each other [ 38 ]. However, the additive effects of sortilin knockdown and AP-5 knockout indicate that AP-5 can also act in a sortilin-independent manner.…”
Section: Discussionmentioning
confidence: 99%
“…We recently demonstrated that following high Mn 2+ exposure, TMEM165 was targeted to lysosomes for its degradation [15]. The targeting molecular mechanism is unclear but recent investigations propose the requirement of Sortilin in the Mn 2+ induced degradation of TMEM165 [16]. The Mn 2+ sensitivity of the mutated forms of TMEM165 was evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Sortilin is a Vps10 orthologue that resides primarily in the Golgi and plasma membrane and mediates lysosomal cargo sorting (Nielsen et al, 1999(Nielsen et al, , 2001Lefrancois et al, 2003;Amengual et al, 2018). Similar to its yeast counterpart, sortilin also regulates the lysosomal sorting of misfolded proteins, such as aggregated GPP130, which is induced by manganese (Tewari et al, 2015;Venkat and Linstedt, 2017). Interestingly, while oligomerization/aggregation is sufficient to trigger lysosomal degradation, trafficking is sortilin independent, suggesting that protein aggregation is necessary, but not sufficient, for sortilin-mediated sorting.…”
Section: Receptor-mediated Gqcmentioning
confidence: 99%